ASKFOOD, a knowledge alliance between businesses and academia in the food-related sectors to leverage innovation and sustainability - P Pittia, G Di Falco, G Schleining, D Tsaltas, J Drausinger, R Verker, ... (My University, 2020)
ASKFOOD, a knowledge alliance between businesses and academia in the food-related sectors to leverage innovation and sustainability/Pittia, P.; Di Falco, G.; Schleining, G.; Tsaltas, D.; Drausinger, J.; Verker, R.; Biesdorf, B.; Medic, H.; Lazaro-Mojica, J.; Sabbatini, G.; Salta, F..-ELETTRONICO.-(2020).((Intervento presentato al convegno 34th EFFoST International Conference Bridging high-tech, food-tech and health: Consumer-oriented innovations.